Theoretical-Methodological Bases of Legal Education of the Future Pedagogue - Inna Shorobura; Vitalii Shyshko (Pedagogical Discourse, 2017)
The article deals with the theoretical-methodological principles of legal education of a pedagogue. The peculiarities of selection and structuring of the legal education of young people, improvement of forms of its organization, methods of measuring the effectiveness have been highlighted. The emphasis is on the new direction – pedagogical law, as a special field of professional pedagogy. The attention is focused on the main emphasis of the content of the legal training of the future teacher. The task of legal education of senior pupils, the ways of its realization in the context of the legal competence of the future teacher have been shown. It is noted that the course of legal training should be of the integrated character, aimed at forming the legal consciousness and behavior, as well as on the implementation of the tasks of pupils’ of senior school age legal education.The need for broad legal education and upbringing of young people is conditioned by the growth of the creative, organizing, coordinating role of the law in social, political and economic development of the society.Legal education is intended to ensure the formation of the high legal culture among young people, which provides for deep legal knowledge and the desire to deepen them, conscious attitude to rights and obligations, respect for the laws and rules of human coexistence, readiness to adhere to and conscientiously fulfill them. The high legal culture of the future pedagogues is one of the basic principles for the establishment of civil society and the rule of law, realization of democratic freedoms.